Exploring the Chemical Components of Porcelain Tiles Commercially available in Benghazi City, Libya (المجلة العلمية لكلية العلوم, 2024)
This study aimed to assess the chemical composition of porcelain tiles in terms of mass percentages. Samples of porcelain tiles were collected from various markets in Benghazi, Libya. X-Ray Fluorescence Spectrometer was utilized to determine the chemical components of the tiles. The evaluation criteria for high-quality raw mineral materials included high representative oxide content, low impurity oxides, and low loss on ignition (LOI). Notably, a distinct variation in the chemical composition of porcelain tiles was observed. In general, two formulations were identified: one group consisted of tiles with high silica content, elevated levels of alumina and alkaline oxides, and low magnesium oxide (MgO); another group comprised tiles with low silica content, high MgO and alumina content, and relatively lower alkaline oxides. The results revealed the averaged mass percentages of various components in the porcelain tiles: silica (SiO2) showed a resistant characteristic to melting and shrinkage at 44.37%; alumina (Al2O3) played a role in polishing and grinding the tiles at 9.85%; lime (CaO) contributed to enhancing the tiles' resistance against heat and abrasion with a mass percentage of 7.26%; MgO served as a sintering aid at 0.40%; potassium oxide (K2O) improved heat resistance, abrasion resistance, and overall appearance of the tiles at 0.77%; sodium oxide (Na2O) was present at 0.61%; iron oxide (Fe2O3) and titanium oxide (Ti2O) acted as colored impurities at 2.84% and 0.82%, respectively. Additionally, calcite (CaCO3) was identified at 11.68%, aiding in the melting and shrinkage process during heating by releasing CO2.